EFFICIENCY AND SAFETY OF VACCINATION AGAINST CHICKENPOX IN CHILDREN - A.G. Rumyantsev (Union of pediatricians of Russia, 2007)
The article is dedicated to the problem of chicken pox in Russia and across the world, its social and economic aspects. The authors provides the modern information on the existing vaccines, their comparative efficacy in different age groups of the patients, as well as the patients from the high risk groups. The researchers reviewed the contraindications and restrictions against the immunization and analyzed the data on the safety and reactogenicity of the vaccine for the chicken pox prevention.Key words: chicken pox, vaccination, children.